The Influence of Leadership Effectiveness and Organizational Justice on Teacher’s Performance - Agustina, Yayuk; Kristiawan, Muhammad; Rahman, Andi (Yayasan Sembilan Pemuda Indonesia, 2024)
This study aims to determine and analyze the effect of organizational justice leadership effectiveness on teacher’s performance. This refers to the findings of previous researchers on how principal leadership and organizational justice have an impact on teacher’s performance. The novelty in this study is the improvement of teacher’s performance through the level of leadership effectiveness and organizational justice of school principals. This research was conducted at Palembang high schools 1, 2, and 4, with a total of 60 respondents from 150 populations using random sampling techniques. This study uses quantitative research methods. Data were obtained by distributing questionnaires to research subjects with a Likert scale rating scale. The results of the data analysis obtained the conclusion that leadership effectiveness and organizational justice together have a significant influence on teacher’s performance with a percentage value of 34%. This shows the contribution of the level of leadership quality and organizational justice of a leader, namely the principal, to the performance of teachers at school.